Vaccine cold chain management practice and associated factors among health professionals in Ethiopia: systematic review and meta-analysis - Abebaw Wasie Kasahun; Amare Zewdie; Solomon Shitu; Girma Alemayehu (Taylor & Francis Group, 2023)
Abstract Background Administration of potent vaccine in a manner of well-maintained cold chain system is one of the public health focus areas in developing regions of the world. Health professionals' adherence towards good vaccine cold chain management practices is an important element to ensure potent vaccine reached to users. Studies on health professionals' practice on vaccine cold chain maintenance and associated factors in Ethiopia have shown wide variations. The aim of this systematic review and meta-analysis is to produce the overall/pooled prevalence of health professionals' good vaccine cold chain management practice and to identify its associated factors in Ethiopia. Methods Systematic review and meta-analysis was conducted on vaccine cold chain management practice and associated factors among health professionals in Ethiopia. Literature search was made on international data bases using medical subject heading and key words. Data were extracted using Microsoft excel and imported to STATA version 17 for analysis. Heterogeneity was checked using Cochrane Q test and I2 statistics. Weighted inverse variance random effect model was used to estimate the pooled level of good vaccine cold chain management practice among health professionals. Publication bias was checked using funnel plot and using Egger's test. Results A total of ten studies were included in the review. The overall/pooled prevalence of good vaccine cold chain management practice in Ethiopia is 27.48% with 95% CI (25.70-29.26). Having good knowledge on vaccine cold chain management AOR 2.27 95% CI (1.72-2.99), and have received on-job training AOR 6.64 95% CI (4.60-9.57) are factors positively associated with vaccine cold chain management practice among health professionals in Ethiopia. Conclusion The overall/pooled prevalence of good vaccine cold chain management practice is much lower than the expected level. There is a need to plan on-job trainings for all vaccine handlers and other health professionals supposed to work on vaccination program.